The impact on incentives of five years of social security reforms in the UK - Mike Brewer; Tom Clark (Institute for Fiscal Studies (IFS), 2002)
The UK's Labour Government has expanded means-testing of social security but attempted to do so while minimising the disincentive effects typically associated with such an approach. We test whether it has succeeded by reviewing the effect of 5 years of reforms on a range of incentives across the British population, undertaking micro-simulations on survey data. The incentive to enter work increases for the first earner in families, but for second- earners in couples the incentive to work has generally been dulled. Effective marginal tax rates have generally increased for workers, in spite of reductions in benefit withdrawal rates, owing to the increasing numbers facing means-tested benefit withdrawal. Reforms have reduced the number of pensioners facing very high effective marginal rates, but increased the number on moderately high rates. Incentives regarding family life have been affected: partnering has become less financially attractive for low-income individuals; having children has become more financially attractive.
Keywords: H24; H31; 330; Soziale Sicherung; Sozialreform; Ökonomischer Anreiz; Großbritannien